2008
DOI: 10.1369/jhc.2008.950840
|View full text |Cite
|
Sign up to set email alerts
|

Does Immunohistochemistry Allow Easy Detection of Lymphatics in the Optic Nerve Sheath?

Abstract: We evaluated the validity of anti-D2-40 and anti-LYVE-1 (antibodies against lymphatic endothelium) for IHC diagnosis and semiquantification of lymphatic vessels in the dura mater of the intraorbital portion of the human optic nerve (ON). Fourteen specimens were analyzed using light microscopy within 12 hr postmortem. We found in all specimens that both D2-40 and LYVE-1 stained lymphatic vessels as well as venules and arterioles. Our findings show lymphatic vessels in the meninges of the intraorbital portion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 30 publications
3
27
0
4
Order By: Relevance
“…However, a larger number of eyes from young children need to be analyzed to confirm this observation. We also failed to find lymphatics/D2-40 positive structures in the ciliary body as was reported by Yucel et al (2009) but could confirm podoplanin expression in the optic nerve sheaths which was interpreted as labeling of lymphatic vessels in the dura mater of the optic nerve and as a nonvascular pattern in the arachnoid mater by others Killer et al, 2008). The latter in particular suggests that podoplanin is not a selective marker for lymphatics (Killer et al, 2008).…”
Section: Expression Of Podoplanin In Our Cohort In Comparison With Thsupporting
confidence: 64%
See 2 more Smart Citations
“…However, a larger number of eyes from young children need to be analyzed to confirm this observation. We also failed to find lymphatics/D2-40 positive structures in the ciliary body as was reported by Yucel et al (2009) but could confirm podoplanin expression in the optic nerve sheaths which was interpreted as labeling of lymphatic vessels in the dura mater of the optic nerve and as a nonvascular pattern in the arachnoid mater by others Killer et al, 2008). The latter in particular suggests that podoplanin is not a selective marker for lymphatics (Killer et al, 2008).…”
Section: Expression Of Podoplanin In Our Cohort In Comparison With Thsupporting
confidence: 64%
“…We also failed to find lymphatics/D2-40 positive structures in the ciliary body as was reported by Yucel et al (2009) but could confirm podoplanin expression in the optic nerve sheaths which was interpreted as labeling of lymphatic vessels in the dura mater of the optic nerve and as a nonvascular pattern in the arachnoid mater by others Killer et al, 2008). The latter in particular suggests that podoplanin is not a selective marker for lymphatics (Killer et al, 2008). It seems worth noting that we found a non-vascular, non-lymphatic pattern of podoplanin labeling also in the suprachoroidal space, the arachnoid/optic nerve sheaths (and also the meninges (Nakamura et al, 2006)), and the trabecular meshwork with the latter two being involved in fluid circulation (liquor resp.…”
Section: Expression Of Podoplanin In Our Cohort In Comparison With Thsupporting
confidence: 57%
See 1 more Smart Citation
“…In fact, the existence of orbital lymphatic vessels has been debated due to the lack of proof of their existence in the orbital fat and extraocular muscles. Only recently has it been shown that a few lymphoid capillaries are present in the arachnoid and dura mater of the intraocular part of the optic nerve (Fogt et al 2004;Gausas et al 2007;Killer et al 2008). Therefore, it is speculated that the main supply of lymphocytes to the orbit comes from the orbital part of the lacrimal gland if needed, where lymphatic cells are abundant (Dickinson & Gausas 2006).…”
Section: Immunology Of the Orbitmentioning
confidence: 99%
“…This thin intralobular lymphatic network may play a key pathophysiological role in a wide variety of alveolar and interstitial lung diseases and requires further investigation. LYMPHATIC VESSELS are present in almost all tissues except for avascular structures and rare vascularized organs such as brain and retina, although they have been recently described in the optic nerve sheath (Killer et al 2008). They constitute a one-way open-ended network running alongside the blood microvasculature.…”
mentioning
confidence: 99%